2020
DOI: 10.3390/s20236993
|View full text |Cite
|
Sign up to set email alerts
|

Defect Classification of Green Plums Based on Deep Learning

Abstract: The green plum is rich in amino acids, lipids, inorganic salts, vitamins, and trace elements. It has high nutritional value and medicinal value and is very popular among Chinese people. However, green plums are susceptible to collisions and pests during growth, picking, storage, and transportation, causing surface defects, affecting the quality of green plums and their products and reducing their economic value. In China, defect detection and grading of green plum products are still performed manually. Traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In addition, ref. [14] used an improved VGG network to detect and classify green plum defects into rot, cracks, rain spots, scars, and intact skin. Compared to our study, their developed VGG model achieved lower recall, precision, and F1-score of 78, 93 and 85% for crack detection in green plums under controlled imaging conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ref. [14] used an improved VGG network to detect and classify green plum defects into rot, cracks, rain spots, scars, and intact skin. Compared to our study, their developed VGG model achieved lower recall, precision, and F1-score of 78, 93 and 85% for crack detection in green plums under controlled imaging conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the R-FCN ResNet101 had the best overall performance in detection speed and accuracy [13]. Likewise, a CNN and a computer vision method to classify defects and damages of green plums was adopted [14]. The developed CNN model was based on the VGG network architecture combined with a stochastic weight averaging optimizer and trained weights on ImageNet.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing growth of research focusing on plant disease classification in recent years aiming to develop effective plant diagnostics systems for farmers [ 21 , 22 , 23 ]. A variety of Artificial Intelligence (AI) methods have been adopted in classifying and detection various plant diseases such as olive [ 24 ], pomegranate [ 25 ], plum [ 26 ], rice [ 27 ], tomato [ 28 ], cassava [ 29 ], mango [ 30 ], tea leaf [ 31 ], apple [ 32 ], citrus [ 33 ], oranges [ 34 ], etc.…”
Section: Related Workmentioning
confidence: 99%
“…To avoid the above problems and forgo the dependence on artificial feature extraction, increasingly, many deep learning methods (e.g., deep belief network (DBN) [ 8 ], convolutional neural network (CNN) [ 9 ], auto-encoder (AE) [ 10 ] and stacked denoising auto-encoder (SDAE) [ 11 ]) are being presented to autonomously mine the representative diagnostic information hidden in the raw data and have received great attention in intelligent fault diagnosis. Shao et al [ 12 ] presented a novel method, called an adaptive deep belief network (DBN), with a dual-tree complex wavelet packet (DTCWPT) to process bearing vibration signals and achieve fault diagnosis of rolling bearings.…”
Section: Introductionmentioning
confidence: 99%